Analysis of beneficial management practices to mitigate environmental impacts in dairy production systems around the Great Lakes. (November 2019) - Kim, Daesoo; Stoddart, Nick; Rotz, C. Alan; Veltman, Karin; Chase, Larry; Cooper, Joyce; Ingraham, Pete; Izaurralde, R. César; Jones, Curtis D.; Gaillard, Richard; Aguirre-Villegas, Horacio A.; Larson, Rebecca A.; et al.
Abstract: The influence of farm-specific beneficial management practices (BMPs) on a set of comprehensive environmental impacts was characterized and quantified for two representative dairy farms in the Great Lakes region (a large 1500-cow farm in New York (NY) and a smaller 150-cow farm in Wisconsin (WI)). Comparative benefits or drawbacks of the effect of the adoption of selected management scenarios to environmental impacts were estimated by coupling the output from the Integrated Farm System Model (IFSM) to provide lifecycle inventory data for SimaPro © . The small dairy farm in WI generated a consistently larger carbon footprint than the large dairy farm in NY due to greater enteric methane (CH4 ) emissions from different feeds fed and greater nitrous oxide (N2 O) emissions from the bedded pack housing facility for young stock. The flare scenario of burning biogas produced in a covered manure storage on the small farm and a whole-farm mitigation plan of combined feed, field, and manure management in the large farm demonstrate significant potential to reduce overall carbon footprint by 20.0% and 25.8%, respectively, compared to the baselines. The assessments of selective impact categories such as fossil energy use, water use, land occupation, aquatic eutrophication, terrestrial acidification, respiratory effects, human toxicity, and ecotoxicity are discussed and highlight hot spots relevant for sustainable dairy farm management. Normalization analysis indicates that eutrophication potential is the largest relative impact profile, which suggests that efforts to mitigate eutrophication can achieve relatively greater environmental impact reduction. Although this study identifies the beneficial adaptation of sustainable dairy production practices on individual impact profiles, trade-offs between impact categories make the analysis more complex when considering the comprehensive suite of environmental impacts. Highlights: IFSM was coupled with LCA software to evaluate dairy production practices. Benefits of BMP adoption are presented for selective impact indicators. Manure management practices show the greatest potential to mitigate GWP. Combined whole-farm mitigation plans reduced all environmental impacts. Trade-offs exist between impact indicators among farm-specific BMPs.